Comparison of passive versus active transcutaneous bone anchored hearing devices in the pediatric population - Nael M. Shoman; Usman Khan; Paul Hong (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective Transcutaneous bone anchored hearing devices (BAHDs) were introduced in an effort to avoid potential complications associated with the abutment of percutaneous BAHDs. Transcutaneous BAHDs can be active or passive. While studies have demonstrated good outcomes with both, a direct comparison of audiological and clinical outcomes of these devices in the pediatric population has not yet been studied. Study design Retrospective, multicenter study. Setting Two tertiary academic centers. Methods Between 2015 and 2019, all patients who received an active transcutaneous BAHD (Bonebridge, BB) at one center, and patients that received a passive transcutaneous BAHD (Attract, AT) at another center, were included in this study. Exclusion criteria included age > 18 years, and mixed hearing loss or single-sided deafness. Study outcomes included patient demographics, indications, complications and preoperative and one-year postoperative audiometric data. Results Eighteen BB and eight AT patients met the inclusion criteria. The age range was 5–16 years. There were no significant differences in complication outcomes. Both devices demonstrated similar mean improvements in hearing thresholds at frequencies of 250 Hz (38 dB Active vs. 38 dB Passive), 500 Hz (34 dB vs. 42 dB), 1000 Hz (34 dB vs. 40 dB) and 2000 Hz (31 dB vs. 22 dB). The BB was significantly more effective at frequencies of 4000 Hz (28 dB vs. 7 dB) and 8000 Hz (29 dB vs. 6 dB) (p < 0.05). Conclusion This is the first study comparing audiological outcomes between an active and a passive transcutaneous BAHD in the pediatric population. While both devices improved audiometric outcomes in the low and mid frequencies, the active BAHD demonstrated significantly better outcomes in the higher frequencies. Graphical Abstract